2019
DOI: 10.1002/em.22296
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of trace elements and KRAS mutations in pancreatic ductal adenocarcinoma

Abstract: Trace elements are a possible risk factor for pancreatic ductal adenocarcinoma (PDAC). However, their role in the occurrence and persistence of KRAS mutations remains unstudied. There appear to be no studies analyzing biomarkers of trace elements and KRAS mutations in any human cancer. We aimed to determine whether patients with KRAS mutated and nonmutated tumors exhibit differences in concentrations of trace elements. Incident cases of PDAC were prospectively identified in five hospitals in Spain. KRAS mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 73 publications
0
23
1
Order By: Relevance
“…Although Ni is considered a carcinogen, it has been shown to exhibit an inverse correlation between Ni content and the incidence of PC (31,32). One report demonstrated a positive correlation between Ni content and PC involving KRAS mutations (51). There is a mounting body of evidence that supports Ni involvement in an array of pancreasrelated dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although Ni is considered a carcinogen, it has been shown to exhibit an inverse correlation between Ni content and the incidence of PC (31,32). One report demonstrated a positive correlation between Ni content and PC involving KRAS mutations (51). There is a mounting body of evidence that supports Ni involvement in an array of pancreasrelated dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, large amounts of whole grains, which are good sources of Se, including whole meal pasta and wheat, sourdough bread, stoneground wheat bread, and brown rice, are recommended by the MD (135). Higher levels of Se appeared protective for both mutated and KRAS wild-type PDAC (136). Amaral et al (137) found that high concentrations of Se were inversely associated with the risk of exocrine PC.…”
Section: Micronutrients and Pcmentioning
confidence: 99%
“…Second, in the specific presence of catalytic metals, such as iron and copper, vitamin C may become a pro-oxidant and behave as an anti-cancer agent, e.g., via production of H 2 O 2 [ 196 , 197 ]. Levels of both copper and iron tend to be higher in PDAC [ 198 , 199 ]. Accordingly, vitamin C may exert a protective role against PDAC.…”
Section: Dietary Considerationsmentioning
confidence: 99%